KAJIAN KEMANDIRIAN KEUANGAN PEMERINTAH DAERAH SEBELUM DAN SESUDAH KEBIJAKAN DANA DESA - Annafi Indra Tama (Jurnal Ekonomi Dan Bisnis, 2018)
This research aimed to find out the differences in financial independence of the East Java provincial government before and after the village fund policy from 2013-2016. The method used in this study is descriptive analysis using secondary data and data collection methods through documentation and literature study. Regional financial independence is measured three financial ratios were, the independence ratio, effectiveness and efficiency. Results of this study it can be seen that in measuring regional financial independence there is a significant change after the enactment of the village fund policy both from the measurement of the independence ratio, effectiveness, and regional financial efficiency. In the independence ratio has decreased after the enactment of the village fund policy, Sampang District. The effectiveness ratio shows results before village fund policy is better than after village funds. Conversely, the efficiency ratio shows better results after the village fund policy. It can also be seen in the measurement of financial independence that training is needed for local governments to be able to manage finances well and not depend on the central government.Keywords: Regional Financial Independence, Policy of Villages